2007
DOI: 10.1007/s10561-007-9053-0
|View full text |Cite
|
Sign up to set email alerts
|

Fresh frozen homologous bone in oral surgery: case reports

Abstract: Intraoral bone defects may be treated using autologous grafts, homologous grafts, heterologous grafts or synthetic products. Autologous bone is now considered the gold standard for bone grafting procedures. Homologous fresh frozen bone, provided by bone banks, is frequently utilized by orthopaedic surgeons because it is considered a safe material from immunological and viral points of view. In the cases reported here, homologous bone was used to repair some osseous defects without changing the surgical protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
(18 reference statements)
1
24
0
Order By: Relevance
“…Clinically, allografts harvested from both the hip and the femur seemed to be a predictable alternative to autogenous bone grafts when used for alveolar ridge reconstruction before implant placement. The reliability of the femoral head to repair osseous defects was pointed out in a case series by D'Aloja et al, 21 who found good osseointegration of the grafts with no signs of tissue necrosis or immunological reactions. Subsequently, the same group treated 14 patients with FFB grafts, reporting an overall success rate of 100% when implants were placed from 4 to 8 months after the reconstructive procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Clinically, allografts harvested from both the hip and the femur seemed to be a predictable alternative to autogenous bone grafts when used for alveolar ridge reconstruction before implant placement. The reliability of the femoral head to repair osseous defects was pointed out in a case series by D'Aloja et al, 21 who found good osseointegration of the grafts with no signs of tissue necrosis or immunological reactions. Subsequently, the same group treated 14 patients with FFB grafts, reporting an overall success rate of 100% when implants were placed from 4 to 8 months after the reconstructive procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Several authors are recently reporting about the use of FFB in oral and maxillofacial surgery (D'Aloja et al 2008;Carinci et al 2009). FFB showed satisfactory biological properties such as its osteoconductive and osteoinductive properties, as well as its biomechanical behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The osteoinductive potential, which represents the most important characteristic of this material, has been recently demonstrated (Rodella et al 2010). Another relevant property is the absence of immunogenity: it is well known that this material in not responsible for non-self reactions (D'Aloja et al 2008). Thanks to its osteoinductive behavior, FFB can be used for filling bone defect after cyst enucleation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to obtain the success of implant therapy, in the preliminary stages it is essential to assess and classify the amount of available bone. In fact, this evaluation is fundamental for the correct implant placement, according to the principles of modern prosthetically driven implant placement [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Autologous bone is typically harvested from intraoral sources [5] as the chin, the mandibular ramous, the tuber maxilla or from extraoral sources as the iliac crest, the fibula, and even parts of the skull [6]. Other graft materials, which are used in clinical practice, are the xenograft bone substitutes, derived from a species other than human, such as bovine, the allograft bone, like autogenous bone which is derived from humans, and at last, the artificial bone, such as bioglass, hydroxyapatite, or calcium phosphate [2]. For the reconstruction of extended bone defects, autologous or homologous bone grafts are preferred, in form of blocks, in order to restore the correct vertical and/or horizontal dimensions.…”
Section: Introductionmentioning
confidence: 99%